2020
DOI: 10.1021/acs.jpcc.0c06765
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Pt and Cd Codoping to Icosahedral Au13 Superatoms

Abstract: We synthesized a new trimetallic cluster [PtCdAu 23 (SC 2 H 4 Ph) 18 ] − , which has an icosahedral Pt@CdAu 11 superatomic core with eight electrons, and investigated how the electronic structure and optical properties of the Au@Au 12 superatomic core of [Au 25 (SC 2 H 4 Ph) 18 ] − are affected by codoping of group X and XII atoms. Spectroscopic and electrochemical measurements showed that the HOMO−LUMO (HL) gap of Pt@ CdAu 11 is larger than that of Au@Au 12 and that the photoluminescence quantum yield (PLQY) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…This structure contains two counterions PPh 4 + , suggesting that the synthesized NC exists in a dianionic form ((PPh 4 + ) 2 [RhHAg 24 (SPhMe 2 ) 18 ] 2− ). In addition, the results of occupancy analysis revealed that the center doping with Rh atoms produced a better fit with lower converged shift value and R 1 index (0.001 and 5.30 %, respectively) than those obtained after surface doping (−0.192 and 5.36 %, respectively), confirming that Rh occupied the central cluster position [15] . The overall framework structure of [RhHAg 24 (SPhMe 2 ) 18 ] 2− was similar to those of [MAg 24 (SPhMe 2 ) 18 ] 2− (M=Ni, Pd, and Pt) NCs [7e, 16] .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This structure contains two counterions PPh 4 + , suggesting that the synthesized NC exists in a dianionic form ((PPh 4 + ) 2 [RhHAg 24 (SPhMe 2 ) 18 ] 2− ). In addition, the results of occupancy analysis revealed that the center doping with Rh atoms produced a better fit with lower converged shift value and R 1 index (0.001 and 5.30 %, respectively) than those obtained after surface doping (−0.192 and 5.36 %, respectively), confirming that Rh occupied the central cluster position [15] . The overall framework structure of [RhHAg 24 (SPhMe 2 ) 18 ] 2− was similar to those of [MAg 24 (SPhMe 2 ) 18 ] 2− (M=Ni, Pd, and Pt) NCs [7e, 16] .…”
Section: Resultsmentioning
confidence: 74%
“…Thes ingle crystal structure presented in Figure 2a [13] In addition, the results of occupancy analysis revealed that the center doping with Rh atoms produced abetter fit with lower converged shift value and R 1 index (0.001 and 5.30 %, respectively) than those obtained after surface doping (À0.192 and 5.36 %, respectively), confirming that Rh occupied the central cluster position. [15] Theo verall framework structure of [RhHAg 24 (SPhMe 2 ) 18 ] 2À was similar to those of [MAg 24 (SPhMe 2 ) 18 ] 2À (M = Ni, Pd, and Pt) NCs. [7e, 16] Owing to the low electron density of hydrogen, the position of Hdopant could not be determined by SC-XRD.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, the results of occupancy analysis revealed that the center doping with Rh atoms produced abetter fit with lower converged shift value and R 1 index (0.001 and 5.30 %, respectively) than those obtained after surface doping (À0.192 and 5.36 %, respectively), confirming that Rh occupied the central cluster position. [15] Theo verall framework structure of [RhHAg 24 (SPhMe 2 ) 18 ] 2À was similar to those of [MAg 24 (SPhMe 2 ) 18 ] 2À (M = Ni, Pd, and Pt) NCs. [7e, 16] Owing to the low electron density of hydrogen, the position of Hdopant could not be determined by SC-XRD.…”
Section: Angewandte Chemiementioning
confidence: 84%
“…In particular, there is a lot of untapped heterometallic bonding between immiscible elements because their pure compounds are unavailable at both the bulk and atomic scale. Nevertheless, such heterometallic bonds should not be ignored, as they could provide important information regarding the design of sub-nano alloy particles (atom-hybridization) 45 47 or high-entropy alloys 48 .…”
Section: Introductionmentioning
confidence: 99%